Identificação de deslocamentos de baixa amplitude e frequência utilizando uma câmera digital - Rissá, Henrique Sidney (2017)
This work exposes the possibility of using a digital camera to detect and acquire dynamic data of small displacements. The technique uses the digitization and post-processing of the images of a video, analyzing them frame by frame, over the total recording time. The displacement data were acquired simultaneously by a conventional method and the one developed in this study. For the conventional method a proximity sensor was used, which had its data collected through an acquisition system. For the present methodology, a digital camera and a dial indicator coupled to the structure of interest were used. The acquisition was performed indirectly, monitoring the angular displacement of a target positioned on the dial indicator hand, which is rigidly coupled to the point of interest. This procedure was adopted due to the magnitude of the displacements being small, which would make direct measurement impossible, mainly due to the resolution of the camera used. In this way, it was possible to compare the signals acquired by means of the proposed technique with a reference standard. During the initial tests, a vibration generator, known as an electromechanical Shaker and a proximity sensor, were used in order to validate the developed methodology. Subsequently, the tests were directed to the application of the technique to equipment under actual operating conditions. Thus, the proposed technique was submitted to analysis performed in a rotary machine, in which was possible to analyze its effectiveness in relation to conditions normally found in industrial plants. In this case, the proximity sensor was also used for the purpose of comparing the acquired data between the two methods.